INNOVATIVE APPROACHES TO THE APPLICATION OF SCIENTIFIC RESEARCH IN THE FIELDS OF HISTORY (Universal International Scientific Journal, 2026)
This scientific article analyzes modern methods of applying scientific research inhistory, in particular, the role of digital history, GIS technologies and 3D modeling. The study coversthe issues of preserving and promoting historical heritage by synthesizing traditional methodologywith innovative approaches. The purpose of the study is to assess the effectiveness of integratingscientific developments in history into education, museum work and political decision-makingprocesses, and practical recommendations are developed using the example of the history ofUzbekistan.
Keywords: Digital history; innovation; methodology